The Political Theory of Judith N. Shklar Exile from Exile - Hess, Andreas; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Judith Shklar called for a radical shift in political theory, toward a view of the history of ideas through the lens of exile. Hess takes this lens and applies it to Shklar's own life and theoretical work.
Keywords: Social sciences; Political science; Political theory; World politics; Political philosophy; Social justice; Human rights